PERTANGGUNGJAWABAN PARA PIHAK DALAM PEMBIAYAAN DENGAN JAMINAN GADAI EMAS MELALUI PEGADAIAN PEMERINTAH DAN PERGADAIAN SWASTA (Studi di PT. Pegadaian (Persero) dan PT. Budi Gadai Indonesia) - FINNA NAZRAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Prof. Dr. Hasim Purba, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHumPeople’s economic difficulties today force them to need more budget to fulfill theirlife necessities. They can either apply for a loan to banks or other financial institutions.Due to its complicated procedures, difficult requirements, and particular collateral, pawnservice becomes an alternative. The most frequently pawned goods is gold because it is apromising investment goods. The research problems are about the status of all parties inthe financing using pawned gold in public and private pawnshops, legal liabilities of thecreditor if the pawned goods are lost or broken, and the legal liabilities of debtor ifownership of the pawned gold is illegal.The results of the research demonstrate that, regarding the legal status of allparties in which there is a borrower i.e. the debtor and a pawn broker i.e. the creditor, allparties have equal rights and obligations that they have to fulfill in order to run the goldpawning process well without any obstacles. The legal liabilities for the gold which ispawned, lost, or broken, is that the creditor is responsible to compensate all loss that hasbeen intentionally and unintentionally caused, since pawned goods are not theresponsibilities of the debtor. Regarding the legal liabilities of the debtor, if the pawnedgoods are proven to be illegally possessed, is that the debtor has to be responsible for allloss endured by the real owner and the creditor who provided the financing.Keywords : Gadai Emas, Jaminan Emas, Pembiayaan Gadai